2019
DOI: 10.1088/1361-6463/ab2b27
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic electro-osmotic flow of Maxwell fluids with patterned charged surface in narrow confinements

Abstract: We study the magnetohydrodynamic electro-osmotic flow of Maxwell fluids through two microparallel plates with patterned charged surfaces. The combined influences of two imposed time periodic electric fields (one along the lateral direction and the other along the axial direction) and an external vertical magnetic field are taken into account. The flow is driven by Lorentz force and electric field force and is 2D due to charge modulated surfaces. Upon the assumptions of the Debye-Hückel linearization, the analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…The simple non-Newtonian fluids models mainly include Power-law fluids model, Oldroyd-B fluids model, Maxwell fluids model, and Jeffreys fluids model. Some relevant studies on EOF of simple non-Newtonian fluids can be seen from the list of reference [20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The simple non-Newtonian fluids models mainly include Power-law fluids model, Oldroyd-B fluids model, Maxwell fluids model, and Jeffreys fluids model. Some relevant studies on EOF of simple non-Newtonian fluids can be seen from the list of reference [20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…According to the superposition principle, the equation and boundary conditions are divided into three parts, so the solution of the equation can be expressed as follows [38]:…”
Section: Edl Potential Distributionmentioning
confidence: 99%
“…The pioneering work belongs to periodically alternating stripes of wall potentials [21][22][23][24][25] that generally induce recirculating flow regions appearing along the longitudinal coordinate. Nonuniformity of wall potential causing increased dispersion [26,27] and mixing efficiency [28][29][30] in EOF has been the object of many studies in decade years. Through an analytical study for EOF in a slit microchannel with axial step zeta potential, Ng and Chen [31] suggested that transverse mixing can be more effectively achieved when there is a bigger step change of the wall potentials.…”
Section: Introductionmentioning
confidence: 99%